The genus scleria in colombia (1948)
Since the publication of my revision of the American species of the genus Scleria (*), continued field work and herbarium studies have brought to light numerous new distributional records for Colombia. In particular, the explorations of Dr. José Cuatrecasas, and of numerous botanists on the. Staff of the Foreign Economic, Administration have resulted in the discovery of several species new to Colombia and at least one new to science.